Sugar level modeling among Kelantanese using structure equation techniques: a case study - Mat Yudin, Zainab; Wan Ahmad, Wan Muhamad Amir; Mohd. Noor, Nor Farid; Yaacob, Lili Husniati; Mohd Ibrahim, Mohamad Shafiq; Aleng, Nor Azlida (Pushpa Publishing House, 2018)
Sugar control in patients with type 2 diabetes mellitus is a crucial part of managing the disease to ensure the progress of further complication of the cardiovascular disease. The aim of this case study is to look into the factors which have a relationship with sugar level among our study sample using a structural equation technique. The sugar level was assessed as fasting blood sugar and Hemoglobin A1c. We examined four main factors which consist of physical factor, biochemistryfactor, cholesterol factor and enzyme factor. From this study, we evaluated factors which significantly have a relationship with the sugar level and these factors were uric acid creatinine urea weight BMI, and tryglicerides There were multidirectional effect and relationship between few factors with their underlying items and the fasting blood sugar or Hemoglobin A1c.